Antenatal Consultation and Postnatal Stress in Mothers of Preterm Neonates (A Two-Center Observational Case-Control Study) - Elisabeth Pichler-Stachl; Elisabeth Pichler-Stachl; Elisabeth Pichler-Stachl; Nariae Baik-Schneditz; Bernhard Schwaberger; Berndt Urlesberger; Gerhard Pichler; Gerhard Pichler; Gerhard Pichler; Po-Yin Cheung; Po-Yin Cheung; Georg M. Schmölzer; et al. (Frontiers Media S.A., 2017)
BackgroundDuring antenatal consultation of women hospitalized for preterm labor, information of possible adverse outcomes is provided. This may however create additional maternal stress and raise some ethical concerns.ObjectiveThe aim of the present study was to evaluate the influence of antenatal consultation by a neonatologist on maternal stress after delivery of a preterm infant admitted to NICU.MethodsIn this study, secondary outcome parameters of a prospective two-center pilot observational study were analyzed. Mothers of preterm neonates < 36 weeks of gestation admitted at two tertiary-level Neonatal-Intensive-Care-Units (NICU) were included. Maternal stress was assessed with the Parental-Stress-Scale:NICU (PSS:NICU) within 72 h after birth. PSS:NICU measures three scales: "relationship and parental role," "sights and sounds," and "baby looks and behaves." Maternal sociodemographic data were collected by questionnaire administered at the same time. Mothers who received antenatal neonatal consultation were matched for gestational age and compared to mothers who had no antenatal consultation by a neonatologist.ResultsA total of 46 mothers of preterm neonates were included, 23 mothers in each group. There was no significant difference in sociodemographic data between the two groups regarding neonates and mothers. There were no significant differences between the two groups regarding stress scales of "sights and sounds" (2.00 ± 0.76 versus 2.19 ± 0.79; p = 0.402), "looks and behaves" (2.55 ± 0.90 versus 2.48 ± 0.94; p = 0.732) and "relationship and parental role" (3.28 ± 1.23 versus 3.46 ± 1.07; p = 0.517).ConclusionOur study demonstrated that antenatal consultation by a neonatologist had no substantial influence on postnatal maternal stress in mothers of preterm neonates admitted to the NICU.